2022
DOI: 10.1021/acs.chemmater.2c00640
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Indium Phosphide Quantum Dot Properties from Synthetic Procedures Using Machine Learning

Abstract: The prediction of chemical reaction outcomes using machine learning (ML) has emerged as a powerful tool for advancing materials synthesis. However, this approach requires large and diverse datasets which are extremely limited in the field of nanomaterials synthesis, due to inconsistent and nonstandardized reporting in the literature, and a lack of understanding of synthetic mechanisms. In this study, we extracted parameters of InP quantum dot (QD) syntheses as our inputs, and resultant properties (absorption, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Nguyen et al recently used machine learning models comparing over 200 published InP QD syntheses to investigate trends in InP syntheses and found that annealing temperature, annealing time, and the presence of zinc additives were the most influential parameters studied when predicting optical peaks and nanocrystal size . The first two make sense considering the significant role annealing temperature and time play in nucleation and growth kinetics.…”
Section: Indium Phosphide Nanocrystal Synthesismentioning
confidence: 99%
“…Nguyen et al recently used machine learning models comparing over 200 published InP QD syntheses to investigate trends in InP syntheses and found that annealing temperature, annealing time, and the presence of zinc additives were the most influential parameters studied when predicting optical peaks and nanocrystal size . The first two make sense considering the significant role annealing temperature and time play in nucleation and growth kinetics.…”
Section: Indium Phosphide Nanocrystal Synthesismentioning
confidence: 99%
“…Nonetheless, combining the In and P source into a single molecule often results in a stable solid under ambient conditions, a desirable trait for industrial applications. 17 In addition, the preformed bonds between the metal and chalcogenide ensure fewer defects are present within the crystal matrix. Finally, single-source precursors simplify the nucleation process by slowing down the conversion rate of the group V precursor, perhaps the greatest limitation of binary reactions.…”
Section: Outlook On Binary Approaches Versus Sspsmentioning
confidence: 99%
“…In its current form, this protocol has been labelled as the heat-up method and alongside the hot-injection protocol (discussed in more detail in Section 3) represents over 80% of the reported literature. 38 Coordinating solvents, such as the ubiquitous trioctylphosphine (TOP) and trioctylphosphine oxide (TOPO), have been probed as both reaction mediums and stabilising/solvating agents. Notable examples include the synthesis of InP QDs in either a mixture of TOP/TOPO or pure TOP using chloroindium oxalate and P(SiMe 3 ) 3 .…”
Section: Dehalosilylation Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to ELNs, new researchers can easily access current synthesis protocols and also learn what has already been tried within the lab. Last but not least, ELNs represent a huge resource for data-driven discovery, which many materials chemists are pursuing in collaboration with computational scientists. , Using reliable data generated within the same laboratory and under standardized conditions is invaluable for comparison with larger data sets extracted via data mining from the literature, which is challenged by the lack of completeness and reporting standardization across different laboratories . Because ELNs provide the primary interface to research data, an opportunity exists to directly integrate computational approaches in order to automatically derive insights into the data and suggest the next step in the synthesis development.…”
mentioning
confidence: 99%